TRLS-05. A multicenter observational study of Cs-131 seeds embedded in a collagen carrier tile for newly diagnosed and recurrent operable intracranial neoplasms –Trial in progress. (9th August 2021) - Dunbar, Erin; McCracken, D Jay; Nowlan, Adam; Chen, Clark; Dusenbery, Kathryn; Ferreira, Clara; Kotecha, Rupesh; McDermott, Michael; Jaikumar, Sivakumar; Shen, Colette; Monyak, David; Trusheim, John; et al.
Abstract: Background: For patients with operable intracranial neoplasms, there are opportunities to augment local control beyond traditional methods, such as external beam radiation therapy (EBRT), . Brachytherapy, the implantation of radioactive sources into the resection cavity, can be useful in this setting by providing immediate initiation of radiation and limiting the exposure of surrounding normal tissue to radiation. Traditional intracranial brachytherapy methods have been limited by uneven dose distributions, complicated workflows, extended procedural times, the cost of dedicated equipment, and frequent adverse events. To address these issues, a permanently implanted device with Cs-131 radiation seeds embedded in a bioresorbable collagen carrier tile (GammaTile, GT Medical Technologies, Tempe, AZ USA) was developed. Described as surgically targeted radiation therapy (STaRT), it is FDA-cleared for use in newly-diagnosed malignant intracranial neoplasms and recurrent intracranial tumors, including brain metastases, and has demonstrated excellent safety and local control in early commercial use. The primary objectives of this multicenter, prospective, observational (phase IV) registry study [NCT04427384] are to evaluate "real-world" clinical outcomes and patient-reported outcomes that measure the safety and efficacy of STaRT using the device. Methods: Subjects (N=600) at up to 50 enrolling sites undergoing resection of brain tumors of any pathology with intra-operative GammaTile placement are eligible for enrollment. We project 40% of enrollees to have brain metastasis. Tumor pathology, overall survival, radiation- and surgery-related adverse events, quality of life, serial MRIs, and timing of surgical bed recurrence and/or distant recurrence will be collected. The powered primary endpoint for recurrent brain metastases, surgical bed-progression free survival, will compare STaRT to standard-of-care benchmarks. This study will be the first observational study of resection plus GammaTile. Results will be used to benchmark clinical outcomes in the real-world setting, allow for comparisons to existing treatments, and facilitate the design of future clinical trials.